A single-center experience on the value of pancreas graft biopsies and HLA antibody monitoring after simultaneous pancreas-kidney transplantation - Becker, Luis Eduardo; Hallscheidt, Peter; Schäfer, Sebastian Markus; Klein, Katrin; Grenacher, Lars; Waldherr, Rüdiger; Macher-Göppinger, Stephan; Schemmer, Peter; Mehrabi, Arianeb; Süsal, Caner; Zeier, Martin; Morath, Christian (Transplantation proceedings, 2015)
Background - In simultaneous pancreas-kidney transplantation (SPKT), monitoring of the pancreas allograft is more complex than the kidney allograft due to difficulties in obtaining pancreas histology and weak clinical evidence supporting the role of donor-specific antibodies (DSA). - Methods - We performed a single-center retrospective analysis of all 17 SPKT recipients who underwent a total of 22 pancreas allograft indication biopsies from October 2009 to September 2012. Fifteen patients had at least 2 DSA measurements: pretransplantation and at the time of biopsy. - Results - All 7 patients (100%) with post-transplantation DSA-positivity (de novo: n = 6; persistent: n = 1) at biopsy had at least 1 rejection episode either of the pancreas (n = 4) or the kidney (n = 3), with 3 antibody-mediated rejections (AMR). In contrast, only 4 of 8 patients (50%) without post-transplantation DSA had evidence of rejection, with 1 AMR. Findings during pancreas allograft biopsy procedures led to a change of immunosuppressive therapy in 11 of 15 (73%) patients. Patient survival, graft survival, and function were not adversely affected by the presence of post-transplantation DSA. One major and 2 minor procedure-related complications occurred during the pancreas biopsies. - Conclusions - In this small retrospective analysis, pancreas allograft histology provided the most therapeutically relevant information, rather than the kidney histology or DSA monitoring.